Diabetes mellitus and arterial hypertension in an urban Los Andes clinic - Lucero, Yalda; González, Carolina; Yentzen, Gladys; De la Fuente, María (Revista Chilena de Salud Pública, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Cardiovascular diseases constitute an important problem as causes of morbimortali(y. They are related to various risk factors, among which arterial hypertension (AHT) and diabetes mellitus ( DM2) stand out. Foreign and national studies describe a frequent association between both factors. In our country information about the clinical and demographic characteristics of patients suffering from both of these conditions is lacking. The purpose of this paper is that of describing the demographic and clinical profiles, as well as risk factors associated to AHT and DM2, in a group of patients receiving medical attention in a clinic of Los Andes. The medical records of 202 patients with AHT and DM2 were checked, and the following items were registered: gender, age, year of AHT diagnosis, DM2, obesity and dyslipidemia, weight at entrance into program and present weight, stature, last glycemia value, A I c glycosylated hemoglobin, arterial pressure and lipidic profile, tobaccoism, non-pharmacologic therapy observance and use of prescribed pharmaceutical products. A 75.7% of the group were females, and the average age at the last control was 66.6 years, 60% being over 65. An important proportion of patients were overweight-obese (82%) and suffering from dyslipidemia (88.Io/o); only I2.4o/o suffered from tobaccoism. The proportion of decompensation for DM2 was 76.2%, for AHT 80%, and 60.7% were uncontrolled in both pathologies. A 93. Io/o received at least one pharmaceutical preparation for the treatment of both AHT and DM2 and only 50% were registered as fulfilling the non-pharmacologic requirements. Obesity was related in a statistically significant way to decompensation for both AHT and DM2, while age < 65 was associated to decompensated DM2. In this group, DM2 and AHT were frequently associated to other cardiovascular risk factors. In obese patients the compensation rate was lower, a fact which suggests a different conduct in this group. The common factor of these pathologies would be the resistance to insulin, which would require an intensive and integral management from the point of view of the metabolic syndrome.